2022
DOI: 10.3390/cancers14143495
|View full text |Cite
|
Sign up to set email alerts
|

HSPG2 Mutation Association with Immune Checkpoint Inhibitor Outcome in Melanoma and Non-Small Cell Lung Cancer

Abstract: Immune checkpoint inhibitors (ICIs) markedly promote the survival outcome of advanced melanoma and non-small cell lung cancer (NSCLC). Clinically, favorable ICI treatment efficacy is noticed only in a smaller proportion of patients. Heparan sulfate proteoglycan 2 (HSPG2) frequently mutates in both tumors. Herein, we aim to investigate the immunotherapeutic and immunological roles of HSPG2 mutations in melanoma and NSCLC. A total of 631 melanoma samples and 109 NSCLC samples with both somatic mutational profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Instead, HSPG2 is associated with tumor progression and poor cancer prognosis ( 46 ). Mutations in this gene can increase a tumor’s responsiveness to immune checkpoint inhibitors and improve the efficacy of targeted drug therapy ( 47 ), but again, there is a lack of basic research on the relationship between this gene and the pathogenesis of PE. Another obvious change in EVTs from the PE group compared to control cells was the downregulation of IGF2 ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, HSPG2 is associated with tumor progression and poor cancer prognosis ( 46 ). Mutations in this gene can increase a tumor’s responsiveness to immune checkpoint inhibitors and improve the efficacy of targeted drug therapy ( 47 ), but again, there is a lack of basic research on the relationship between this gene and the pathogenesis of PE. Another obvious change in EVTs from the PE group compared to control cells was the downregulation of IGF2 ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in different types of cancer, POLE/POLD1 mutations were associated with an elevated TMB and immunogenicity-related signaling pathways, [13] and patients with POLE/POLD1 -mutated tumors had longer overall survival than patients with wild type tumors after immunotherapy. [13–15] Mutations in MUC16 , [16,17] FAT1 , [18] HSPG2 , [19] RELN , [20] and PTPRT [21] were also identified to be associated with a better ICIs prognosis or response rate.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the widespread use of ICI treatments in these two cancer types and the availability of numerous publicly accessible datasets, they are always selected for immune-related research. The main objective of ICI treatment is to kill cancer cells by reactivating CD8 T cell-mediated immune functions [ 2 ]. However, despite the remarkable clinical treatment efficacy, only a smaller proportion of cancer patients are responsive to ICI agents, and highly sensitive indicators of response to such treatments are not yet utilized to evaluate clinical immunotherapeutic benefits [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zhang et al observed that FAT1 mutations were linked to preferable ICI efficacy and immunogenicity in 109 NSCLC patients and validated these connections in 631 melanoma and 1661 pan-cancer patients [ 6 ]. Furthermore, mutations in MUC16 [ 7 ], TP53 [ 8 ], COL3A1 [ 9 ], HSPG2 [ 2 ], POLE [ 10 ], PTPRT [ 11 ], and PPP6C [ 12 ] have been shown to positively connect with ICI therapeutic efficacy. Nevertheless, JAK1/2 [ 13 ] and B2M [ 13 ] mutations were found to be negatively associated with treatment response.…”
Section: Introductionmentioning
confidence: 99%